Impact of agricultural crop type and hunting on bird communities of two villages in Bandung, West Java, Indonesia - LUKMANUL HAKIM; OEKAN S. ABDOELLAH; PARIKESIT; SUSANTI WITHANINGSIH (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Hakim L, Abdoellah OS, Parikesit, Withaningsih S. 2020. Impact of agricultural crop type and hunting on bird communities of two villages in Bandung, West Java, Indonesia. Biodiversitas 21: 57-66. Land use change has occurred in the Upper Citarum Watershed over time, converting tropical rain-forest to man-made cash-crop gardens dominate the agricultural landscape, leaving mixed-garden (talun), rice fields and smallholder plantation. This changes species composition, community structure and animal diversity, especially bird species. The objective of this paper was to study bird structure community in rural agricultural landscape in Upper Citarum Watershed. We conducted the survey from February to March 2018. We surveyed birds at 36 point counts (PCs), each PC's surveyed six times for 15 minutes along total 6 km of transects in the agricultural landscape in Sukapura and Resmi Tingal Village, consisting of 12 PCs in mixed-garden, 12 PCs in homegarden and 12 PCs in cash-crop garden. Twenty-nine bird species, 17 families and 1.103 individuals were recorded; 2 species being protected by Indonesian law in all sites, three Javan Island endemics and one species migrant bird species. The insectivorous birds are dominant with 15 species in all land-use types. Passer montanus and Javan munia were the most common birds in all land-use types with 820 of 1.103 individual birds (74,9%) were of two bird species. Mixed-garden had higher bird diversity, species richness, and evenness index than the homegarden and cash-crops garden because of the complexity of vegetation structure and canopy cover stratification. There was a significant decrease in some bird species which in the previous study was dominant to be reduced even to local extinctions such as Oriental White-eye (Zosterops palpebrosus), Crescent-chested Babbler (Stachyris melanothorax) and Western Yellow Wagtail (Motacilla flava). Decreased bamboo-tree garden as Crescent-chested Babbler habitat is suspected to be the cause of declination of this bird population. In addition, unregulated bird hunting is also one of the causes of the declining bird populations, especially birds with market value. Some species such as Oriental White-eye (Zosterops palpebrosus), Sooty-headed Bulbul (Pycnonotus aurigaster), Great Tit (Parus major), Bar-winged prinia (Prinia familiaris), Javan myna (Acridotheres javanicus) and Spotted dove (Streptopelia chinensis) have rapidly decreased population because of bird hunting activities.